Evaluation of the Electronic ID Card (KTP-El) Registration Service for People with Disabilities in Taman Kota Subdistrict Madiun - Rifqi Akmal Muttaqin; Tjitjik Rahaju; Indah Prabawati; Firre An Suprapto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Civil registration is a basic service that must be accessible to all citizens, including people with disabilities, who often face barriers in obtaining an Electronic Identity Card (KTP-el). This study aims to evaluate the implementation of KTP-el registration services for people with disabilities through the Gajah Mada Service innovation organized by the Madiun City Population and Civil Registration Office in Taman District. The study employs a qualitative approach with a descriptive design. Data were collected through interviews, observations, and documentation, then analyzed using William N. Dunn’s six policy evaluation indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results indicate that the service has been functioning fairly well and has provided benefits in improving access to civil registration services for people with disabilities. However, implementation has not yet been fully optimal, as approximately 20% of people with disabilities in Taman Subdistrict have not yet registered for the e-ID. Identified challenges include a service system that remains passive, limited human resources, internet connectivity issues, information disparities, as well as social and cultural barriers within families and the community. Therefore, continuous improvement efforts are needed to make the service more inclusive, equitable, and effective in reaching all people with disabilities.